As representações da malária na obra de João Guimarães Rosa The portrayal of malaria in the works of João Guimarães Rosa - Norinne Lacerda-Queiroz; Antônio Queiroz Sobrinho; Antônio Lúcio Teixeira (História, Ciências, Saúde: Manguinhos)
O artigo aborda fatores históricos, científicos e literários da malária, com ênfase nas imagens da doença na obra do escritor João Guimarães Rosa. A principal referência para este estudo é o conto "Sarapalha", presente no livro Sagarana. A formação médica do autor somada a suas experiências no interior do país serve de subsídio para a obra, com histórias vivenciadas na rudeza do sertão. Um ponto de destaque no conto é a narrativa da malária na linguagem do sertão, mas com absoluta fidedignidade médico-científica. The article discusses the historical, scientific and literary aspects of malaria, with an emphasis on images of the disease in the work of the writer João Guimarães Rosa. The main reference for this study is the short story "Sarapalha," which is featured in the book entitled Sagarana. The author's medical training together with his experiences in the hinterlands of the country is the subject matter for the work, with stories of the harsh reality of life in the outback. A highlight of the story is the narrative of malaria in the language of the outback, though with absolute medical and scientific precision.